2018
DOI: 10.3389/fbioe.2018.00005
|View full text |Cite
|
Sign up to set email alerts
|

Five Days Granulocyte Colony-Stimulating Factor Treatment Increases Bone Formation and Reduces Gap Size of a Rat Segmental Bone Defect: A Pilot Study

Abstract: Bone is an organ with high natural regenerative capacity and most fractures heal spontaneously when appropriate fracture fixation is provided. However, additional treatment is required for patients with large segmental defects exceeding the endogenous healing potential and for patients suffering from fracture non-unions. These cases are often associated with insufficient vascularization. Transplantation of CD34+ endothelial progenitor cells (EPCs) has been successfully applied to promote neovascularization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…In this study, an increase in the percentage of cartilage formation in the treatment group with a combination of G-CSF and the antagonist CXCR4 [ 36 ]. Research conducted by Herrmann et al also showed similar results, where there was an increase in the formation of cartilage areas in the G-CSF treatment compared to controls [ 28 ].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In this study, an increase in the percentage of cartilage formation in the treatment group with a combination of G-CSF and the antagonist CXCR4 [ 36 ]. Research conducted by Herrmann et al also showed similar results, where there was an increase in the formation of cartilage areas in the G-CSF treatment compared to controls [ 28 ].…”
Section: Discussionmentioning
confidence: 56%
“…therefore the fracture healing effect due to inducing osteoblast cells is not the answer to accelerating the healing process. As previously explained, G-CSF can increase the number of stem cells and it is these stem cells that will produce BMP-2 where BMP-2 expression will recruit stem cells at the fracture site [ [28] , [29] , [30] ]. In addition, from a clinical application point of view, Patients who presented with delayed union did not require surgery [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In children with severe chronic neutropenia, extended G-CSF use correlates significantly with lower BMD but this correlation is not seen in adults [54]. Contrasting this, a recent study in animals showed significantly improved bone formation with G-CSF treatment [55]. Together these data suggest a need for further study into the role of G-CSF in allogenic HSCTrelated loss of BMD.…”
Section: Vitamin D Deficiency: Vitamin D Increases Intestinalmentioning
confidence: 93%
“…Also, HRT can increase the possibility of cardiovascular complications such as thromboembolism and stroke, an important consideration in woman. Breast cancer risk needs to be discussed in detail when estrogen replacement therapy is considered [55]. Finally, bisphosphonate therapy should be started prophylactically in patients who are at high risk of bone loss and fracture or who already have developed osteoporosis [81].…”
Section: Prevention Modalitiesmentioning
confidence: 99%